Decentralized neural control : application to robotics /: application to robotics. (2017) - Garcia Hernandez, Ramon; Lopez-Franco, Michel; Sanchez, Edgar N; Alanis, Alma Y; Ruz-Hernandez, Jose A
No abstract available